(3GdeONd aj Yde CMcGe GdfLhes - (3LYaQ Hf eMeO Hf YeQ GdHdNj, CHh eYTQ , nCoHh nerYnTQ Gdnandcj,J (B272 (3g` s ((3GSMGb Hf eMeO Hf jYbhH Hf GSMGb s)
(3ChdgG (B:s
(3GdaUd GdChd ef GdebGdI GdChdi ai GdebOeI Ef GdSHH GdPi OYGfi Edi JCdja cJGH GdeONd Edi Yde CMcGe GdfLhe s
(3BNQgG (B:s
(3Ef GdWGdY cGf GdLhRGA HYO Pdc GdOQL hdh cGf GdeLghd ced GdcJGH HMeO Gddg s
(3GdYfhGfGJ HNW chais
(3HChdg agQS daUhd GdcJGHs
(3HgG ShGA hWeS hJbWjYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B127 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B148s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B394 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 - (3U (B22 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1643s
Keywords: (3Gdadcs